2018
DOI: 10.1002/ps.4829
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and fitness costs of Spodoptera frugiperda (Lepidoptera: Noctuidae) resistance to spinosad in Brazil

Abstract: The autosomal, incompletely recessive and polygenic resistance to spinosad in S. frugiperda and the fitness costs associated with this resistance can be exploited in IRM strategies to preserve the lifetime of spinosad for control of S. frugiperda in Brazil. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 54 publications
(124 reference statements)
3
104
1
5
Order By: Relevance
“…the resistance loci are in autosomal chromosomes. As in most cases of insecticide resistance, other studies have reported autosomal resistance of S. frugiperda , to lambda‐cyhalothrin, carbaryl, lufenuron and spinosad . For the diamide insecticides, the resistance of P. xylostella and T. absoluta was characterized as autosomal and incompletely recessive dominance …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the resistance loci are in autosomal chromosomes. As in most cases of insecticide resistance, other studies have reported autosomal resistance of S. frugiperda , to lambda‐cyhalothrin, carbaryl, lufenuron and spinosad . For the diamide insecticides, the resistance of P. xylostella and T. absoluta was characterized as autosomal and incompletely recessive dominance …”
Section: Discussionmentioning
confidence: 99%
“…As in most cases of insecticide resistance, other studies have reported autosomal resistance of S. frugiperda, to lambda-cyhalothrin, 25 carbaryl, 23 lufenuron and spinosad. 28,29 For the diamide insecticides, the resistance of P. xylostella and T. absoluta was characterized as autosomal and incompletely recessive dominance. 54,55 Dominance of resistance under field conditions depends on many factors including the concentration applied, the development stage of the insect, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the evolution of resistance of FAW to some Bt proteins expressed in corn in Brazil, the use of chemical insecticides has increased in some corn‐producing regions . However, frequent reports of resistance to major chemical insecticides such as spinosad, lambda ‐cyhalothrin, chlorpyrifos and lufenuron, challenges the control of this pest. Thus, the number of effective modes of action available to implement resistance management strategies, is shrinking.…”
Section: Discussionmentioning
confidence: 99%
“…Such a treatment frequency is conducive to the development of insecticide resistance in FAW, so it is not surprising that high levels of resistance to several chemical classes of insecticides have been reported recently in Puerto Rico . In Brazilian populations of FAW, resistance to a range of synthetic insecticides, addressing different modes of action, including organophosphates, carbamates, pyrethroids, benzoylureas and spinosyns, has been also described …”
Section: Introductionmentioning
confidence: 99%